An Investigation of Concurrent Validity of Fidelity of Implementation Measures at Initial Years of Implementation. (February 2019) - Khoury, Caitlin Rasplica; McIntosh, Kent; Hoselton, Robert
Fidelity of implementation of school practices is crucial to student outcomes. Several types of tools, including self-assessments, are available for measuring fidelity, but little is known regarding the relation of self-assessments of fidelity to fidelity instruments completed with the support of external experts, specifically, during the first few years of implementation. The present study used cross-sectional data from 1, 438 schools to examine relations between fidelity self-assessment and team-based fidelity measures in the first 4 years of implementation of School-Wide Positive Behavioral Interventions and Supports (SWPBIS). Results showed strong positive correlations between fidelity self-assessments and a team-based measure of fidelity at each year of implementation.